2019
DOI: 10.1186/s12885-019-5400-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148b regulates tumor growth of non-small cell lung cancer through targeting MAPK/JNK pathway

Abstract: Background MicroRNA-148b (miR-148b) has been detected in various types of tumors, and is generally viewed as a tumor suppressor. Our previous study found the decreased expression of miR-148b in human non small cell lung cancer (NSCLC) specimens and cell lines. However, the underlying mechanisms of miR-148b in regulating tumor progression remain unclear. Methods Firstly animal experiments were performed to verify whether miR-148b could inhibit the tumor growth. Then, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…A study showed that β-catenin knockdown inhibited metastatic potential, including migration and invasion, and inhibited the brain metastasis of PC14PE6/LvBr4 cells in vivo (20). Further, our results indicated that AC122108.1 is downregulated in PC14/B cells, a highly brain metastatic cell line of LAD, which significantly suppressed the proliferative, invasive, and metastatic potential of these cells (21,22). The results of in vivo and in vitro experiments demonstrated that AC122108.1 plays an important role in regulating the proliferation, cell cycle, apoptosis, invasiveness, migration, and metastasis of LAD.…”
Section: Original Articlementioning
confidence: 50%
“…A study showed that β-catenin knockdown inhibited metastatic potential, including migration and invasion, and inhibited the brain metastasis of PC14PE6/LvBr4 cells in vivo (20). Further, our results indicated that AC122108.1 is downregulated in PC14/B cells, a highly brain metastatic cell line of LAD, which significantly suppressed the proliferative, invasive, and metastatic potential of these cells (21,22). The results of in vivo and in vitro experiments demonstrated that AC122108.1 plays an important role in regulating the proliferation, cell cycle, apoptosis, invasiveness, migration, and metastasis of LAD.…”
Section: Original Articlementioning
confidence: 50%
“…This suggests that miR-148b plays an important role in cancer dynamics, including melanoma. In non-small-cell lung cancer, miR-148b suppresses tumor growth and metastasis by regulating the NF- κ B and MAPK/JNK pathways [ 28 , 29 ]. Leong et al reported that miR-148a/b-3p targets an isoform of RAS-like protein (RALBP1) and thus functions as a tumor suppressor in oral squamous cell carcinomas [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Ang II on myocardial apoptosis in mice was determined by using the Annexin V-FITC/PI cell apoptosis detection kit (KeyGEN BioTECH, Nanjing, China) according to a protocol used previously. 10…”
Section: Methodsmentioning
confidence: 99%